Plantar plate rupture: aetiology, diagnosis and treatment. Issue 1 (February 2023) - Jha, Shilpa; Clark, Callum
Abstract: The fibrocartilaginous plantar plate is a key static stabilizer of the lesser metatarsophalangeal joints and disruption is associated with metatarsalgia which may progress to significant coronal and sagittal plane deformities, most commonly of the second toe. Chronic attrition is by far the most common mode of injury, though rupture can also occur in acute trauma or in association with erosive rheumatoid arthritis. Focal plantar pain and tenderness, positive drawer test, reduced plantar grip strength and lesser toe deformities are key clinical findings. Diagnosis may be further evaluated with plain radiographs and MRI. Clinical and surgical classification systems have been developed expressing the progression from plantar pain without deformity eventually leading to fixed crossover toe. A range of treatment options have been described in the literature including conservative options, osseous decompression techniques, anatomic plantar plate repair and tendon-transfers. There has been increased focus on anatomic surgical repair as a key treatment strategy over the last decade. Whilst promising results in terms of functional outcome are demonstrated in the literature at the short and mid-term, risks of postoperative stiffness and floating toe deformities should not be ignored when counselling patients regarding surgery and conservative treatment should remain first line.